2017
DOI: 10.1021/acs.est.6b06591
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ISCO Treatment on PFAA Co-Contaminants at a Former Fire Training Area

Abstract: The effects of an in situ chemical oxidation (ISCO) treatment aimed predominantly at remediation of chlorinated volatile organic compounds (cVOCs) and perfluoroalkyl acids (PFAAs) co-contaminants were investigated. Soil and groundwater samples were collected before and after an ISCO pilot-scale field test of a peroxone activated persulfate (OxyZone) technology. Statistically significant decreases in PFAA groundwater concentrations were observed in post-treatment samples. Reductions in PFAA aqueous phase concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Researchers have theorized that ozone in the form of nanobubbles can destroy both PFOS and PFOA (Kerfoot, ); however, it appears possible that PFASs may have been foam‐fractionated from solution as a result of the high surface area of the small bubbles formed, as PFASs will distribute to the gas–liquid interface and then partition to the surface of the liquid as foam in a process similar to ozofractionation. The use of persulfate and ozone reported for successful in situ remediation of PFASs may also have suffered from repartitioning of PFASs as a result of ozone‐sparging PFASs to the water table and smear zone (Eberle, Ball, & Boving, ).…”
Section: Destructive Techniquesmentioning
confidence: 99%
“…Researchers have theorized that ozone in the form of nanobubbles can destroy both PFOS and PFOA (Kerfoot, ); however, it appears possible that PFASs may have been foam‐fractionated from solution as a result of the high surface area of the small bubbles formed, as PFASs will distribute to the gas–liquid interface and then partition to the surface of the liquid as foam in a process similar to ozofractionation. The use of persulfate and ozone reported for successful in situ remediation of PFASs may also have suffered from repartitioning of PFASs as a result of ozone‐sparging PFASs to the water table and smear zone (Eberle, Ball, & Boving, ).…”
Section: Destructive Techniquesmentioning
confidence: 99%
“…Competitive decomposition of persulfate and/or oxidizing free radical species may be a cause of reduced destruction of PFAS. Experiments performed with combined oxidant systems reported that chemical oxidation of PFAS could be successful when creating complex chemistries that generate various radical species (Eberle et al., ; ISOTEC, ; Kingshott, ; Pancras et al., ; Suthersan et al., ). However, experimental reactors in this study and other studies designed to enhance generation of multiple free radical species, including using more than one activation method for sodium persulfate, observed reduced degradation of PFOA and other PFAS.…”
Section: Discussionmentioning
confidence: 99%
“…Eberle, Ball, and Boving () reported on field and laboratory tests using a proprietary buffered solution of peroxone brand‐named OxyZone ® (a combination of ozone and hydrogen peroxide activated persulfate). The application also included hydroxypropyl‐β‐cyclodextrin, to promote the desorption of chlorinated volatile organic compound co‐contaminants.…”
Section: Chemical Oxidation Of Pfasmentioning
confidence: 99%
See 2 more Smart Citations